Voices from the Bolivian Altiplano: perspectives on empowerment among Aymara women - Emily Hedin (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
This paper examines the perspectives on empowerment among Aymara women against the concept of empowerment as it evolves in the context of international development. Through the analysis of findings from a series of field observations it was found that Aymara women had a threefold perspectives of empowerment: (1) Empowerment as participation where women could find a voice and take collective action; (2) Empowerment as leadership where women were enabled to take the reins of local change; and (3) Empowerment through conflict where women could open up space and shift roles in adverse situations. The paper concludes by reiterating the need for studies of empowerment to embed the local within the national and global. By identifying the interconnectivity between Aymara women in El Alto and La Paz, national politics, and international scholarship, the paper calls for a framework that captures how institutions, politics, and society construct empowerment.